2009
DOI: 10.2174/157488409787236065
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Modified ‘Dietary Flavonoids’: Are these Viable Drug Candidates for Chemoprevention?

Abstract: The field of chemoprevention continues to be a heavily researched area since a few decades now. Whereas, the dietary intake of flavonoids occur via daily intakes of fruits, vegetables, herbal preparations, beverages etc, it appears that the active ingredients(s) contained in these dietary sources may not reach the required plasma and/or tissue concentrations in vivo to produce the desired pharmacological response expected of these agents. Akin to the common problems of druggability encountered often times in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In mammals, after absorption from the small intestine, flavonoids undergo extensive metabolism, generating different conjugation forms such as glucuronides and sulfates (19,20). The bioavailability of flavonoids is generally low and can be problematic in pharmacological studies (19,21,22), as these conjugation reactions can enhance the elimination of lipophilic xenobiotics (19,21). It has been shown that glucuronidation of flavonoids can influence the bioavailability of flavonoids in mammals partly by changing their permeability and interactions with their putative transporters such as ATP-binding cassette superfamily transporters (19-21, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, after absorption from the small intestine, flavonoids undergo extensive metabolism, generating different conjugation forms such as glucuronides and sulfates (19,20). The bioavailability of flavonoids is generally low and can be problematic in pharmacological studies (19,21,22), as these conjugation reactions can enhance the elimination of lipophilic xenobiotics (19,21). It has been shown that glucuronidation of flavonoids can influence the bioavailability of flavonoids in mammals partly by changing their permeability and interactions with their putative transporters such as ATP-binding cassette superfamily transporters (19-21, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids play various roles in a wide variety of organisms as antioxidants, antibacterial agents, and UV absorbers (19,22,27). We asked whether flavonoids in cocoon shells have functional consequences in silkworm biology.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the phytochemicals including flavonoids are shown more effective beneficial pharmacological properties in vitro than in vivo. This could be due to several reasons including low bioavailability, lack of stability, poor membrane penetration, lack of site specific distribution and rapid elimination of these flavonoids [57]. Introducing structural modifications to flavonoids were found to be effective in enhancing some biological functionality of parent flavonoids.…”
Section: Structurally Modified Flavonoidsmentioning
confidence: 99%
“…2022 Flavonoids, which are ubiquitously distributed in many dietary plant materials, have received a great deal of attention because some of them have been shown to exert various beneficial effects on human health. 23 Apigenin (Figure 1) is abundantly present in common fruits and vegetables, and has gained particular interest in recent years as a beneficial and health-promoting agent because of its low intrinsic toxicity. 24 Apigenin has been demonstrated to possess various clinically relevant properties such as anti-inflammatory, anti-oxidant, antiproliferative and pro-apoptotic activities likely through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%